Choices for spending government revenue: New African oil, gas, and mining economies - Sophie Witter; Maja Jakobsen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper examines a broad range of opportunities for addressing the pressing human development needs of low-income countries by using new oil, gas, and mineral discoveries. It assesses how much of an impact can be made on the funding gaps for health and education by new oil and gas revenues, and what other uses of those revenues are likely to arise. The paper argues that there is a strong case for investing natural resources revenues in social sectors, as they provide an opportunity to help to close the financing gaps in the African countries examined. However, the paper also highlights that the political economy risks of this revenue stream are higher than for other types of revenues. Finally, it illustrates how a simple diagnostic framework can be used to help to guide social sector investment decisions in the light of new natural resources revenues.
Keywords: I15; I18; I22; I25; I28; I38; 330; extractives; education; framework; health; revenue; social protection